Taller "DON T'BE SILENT" en el desarrollo de la producción oral del idioma inglés de los estudiantes del 3º grado del nivel secundario de la Institución Educativa "Santa Rosa" de la ciudad de Tarapoto - 2012 - Navarro Ramirez, Dick Kevin (2013)
This research was made to determine if the Workshop DON'T BE SILENT improve the oral English production skill of students from the 3rd grade of secondary level of Santa Rosa high school of Tarapoto city - 2012. The workshop DON'T BE SILENT developed 8 lessons in 16 pedagogical hours where the activities were developed with strategies, promoting the imagination and creativity of students. The Pre and Post-test were designed on base of 50 questions/items divided by the dimensions with of the English oral production coherence and grammar, fluency and intonation. This was a type of experimental and pre experimental research, the design of the research was with one group, PRE-TEST, POST-TEST or experimental group. For the research, we took a population from the secondary level students of "Santa Rosa" high school of Tarapoto city and we only took the section of 3rd "A" (26 students) as sample. We used the quantitative method in the Pre and Post-test of the Workshop and the qualitative method in terms of the students' report to the workshop for each class. The processing of data for the descriptive statistical analysis (average, standard deviation and the arithmetic media) and the design of the graphics for each information table of the research, was carried out in Excel 2010.To obtain the results, such as: T- tabulated, we used the T student and for the T- calculated, we applied a series of mathematical operations. The results show that the workshop significantly improved the oral English production skill of students, according to Table No. 01, it demonstrates a great improvement among the PRETEST and POST-TEST, 06-16 respectively. Table N º 08, it demonstrates that there is a great significant progress of the students, so the hypothesis test accepts the hypothesis research and rejects the hypothesis null. Conclusions: lt demonstrates the significant effect that the workshop DON'T BE SILENT wich improved the oral English production skill of students from the 3rd grade of secondary "Santa Rosa" high school of Tarapoto city -2012. This is corroborated in Table No. 01, No. 03 and Nº 08, with its respective graphics.